Moralities of wellbeing - Sarah C. White (University of Bath, Centre for Development Studies (CDS), 2018)
This paper is a lightly edited transcript of Sarah's Inaugural Professorial Lecture on April 25, 2018. It draws on primary research in Zambia but also reflects on the promotion of wellbeing in the UK. There are three main points. 1. The need to recover a key promise of the focus on wellbeing, to move from seeing people as objects of policy to recognising them as subjects of their own lives. 2. This means understanding wellbeing as grounded in relationships, not held within the individual. A model of relational wellbeing emerging through the interaction of personal, societal and environmental structures and processes is offered. 3. Recognising people as subjects raises the question of what kind of subjects they are. The paper argues that wellbeing advocates primarily construct people as psychological subjects. The research in Zambia suggests instead that we should view people as moral subjects. This does not mean that people always get things right, but that for most people, much of the time, trying to do so matters. The paper closes by suggesting some implications of a relational approach to wellbeing for policy and practice.
Keywords: 330